Impact of human capital investment and company financial performance in the South African banking industry - Duiker, Ursula Basani (My University, 2017)
The banking industry in South Africa facilitates job creation, the establishment of crucial infrastructure, sustainable development and economic growth for South Africans and the country. It is the largest sector in the South African economy, contributing 21.1% of GDP. In the contemporary South African environment, to compete and attain high performance, banks should position for growth. Research suggests that human capital investment, including training and development and salary spend, play a key role in the companies‟ and industries‟ outputs, given a set of inputs (productivity). Researchers also propose that human capital investment decisions are intrinsically linked to the success of a business and ultimately to the probability of survival. The aim of this study was to assess the relationship between human capital investment (HCI) and company‟s financial performance within the South African Banking industry. This study focuses on the registered banks with the SARB that are listed on the Johannesburg Stock Exchange, excluding the mutual and co-operative banks. The analysis was conducted on six of the seven JSE listed Bank, and these include the top five banks that constitute over 80% of the South African banking industry assets and market share. Data was collected from Annual reports of the banks from 2004 to 2014 to calculate financial performance indicators to conduct a correlation analysis of training and development, average salary spend and financial performance. In summary, the study supports the notion that the correlation of human capital investment with financial performance is subject to the indicator that has been selected to represent performance. Findings concluded that there‟s a strong positive correlation between human capital investment and net profit margin and return on equity indicators that represents profitability of the bank. However, it was also found there is a strong negative correlation between human capital investment and return on assets that represents efficient use of assets and value creation.
MBA Thesis
Keywords: Banks and banking -- South Africa,Human capital -- South Africa, Personnel management -- South Africa.